2007
DOI: 10.3892/or.17.5.1237
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation of intracellular proteins of thyroid lesions

Abstract: Enhanced sialylation represents one of the most frequently occurring alterations of the sugar chain structure in various cancers. However, up to now, sialylation of intracellular proteins of thyroid carcinomas has never been investigated. The aim of this study was comparative analysis of cytoplasmic and nuclear sialoglycoproteins isolated from thyroid benign and malignant tumors as well as non-neoplastic lesions. The sialylation level and types of sialic acid linkages were analysed by lectin blotting and enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…It has been suggested that hyperproliferation of thyroid cancer cells might be related to an overall increasei nO -GlcNAcl evels. [41] Consistent with this hypothesis, we observed qualitatively highers tainingi nt he cancerous tissue (papillary carcinoma) compared to the normal thyroid tissue ( Figure 4A), which was confirmed by the quantification of mean fluorescence intensity (MFI) of the full tissue specimens and coverage area percentageo fO -GlcNAcs ignal ( Figure S9). Interestingly,i n the healthy tissue, O-GlcNAc staining wasl ocated primarilyi n the nucleus, whereas adiffuse cytoplasmic signal was observed for cancerous specimens.…”
Section: Resultssupporting
confidence: 80%
“…It has been suggested that hyperproliferation of thyroid cancer cells might be related to an overall increasei nO -GlcNAcl evels. [41] Consistent with this hypothesis, we observed qualitatively highers tainingi nt he cancerous tissue (papillary carcinoma) compared to the normal thyroid tissue ( Figure 4A), which was confirmed by the quantification of mean fluorescence intensity (MFI) of the full tissue specimens and coverage area percentageo fO -GlcNAcs ignal ( Figure S9). Interestingly,i n the healthy tissue, O-GlcNAc staining wasl ocated primarilyi n the nucleus, whereas adiffuse cytoplasmic signal was observed for cancerous specimens.…”
Section: Resultssupporting
confidence: 80%
“…There is evidence that the intracellular glycosylation changes occurring during carcinogenesis are independent of those that occur on the cell surface or in the blood. Krzeslak et al (32) observed that the sialylation levels of intracellular proteins in thyroid lesions, particularly follicular and papillary carcinomas, were significantly lower than those in non-neoplastic lesions. However, there have been no subsequent confirmatory studies.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-218 inhibited the invasion and migration of colon cancer cells by targeting the PI3K/Akt/mTOR signaling pathway [51]. High glucose promoted tumor invasion and increased metastasisassociated protein expression in human lung epithelial cells by upregulating heme oxygenase-1 via reactive oxygen species or the TGF-ß1/PI3K/Akt signaling pathway [52]. Upregulation of O-GlcNAcylation promoted proliferation in thyroid anaplastic cancer cells via increasing Akt1 activity [53].…”
Section: Figmentioning
confidence: 99%